Isolation, Speciation and antifungal drug susceptibility of Candida species from clinically suspected infections in a tertiary care hospital - Dr Jyoti Gupta; Dr. Harshada Shah (Tropical Journal of Pathology and Microbiology, 1970)
Introduction: The incidence of fungal infections has increased dramatically over the last two to three decades. Study was done on, Clinical samples from suspected patients of candidiasis. Study period was one and a half year from January 2013 to June 2014. Out of 915 clinically suspected samples of candidiaisis processed in the Microbiology Laboratory, 156 (17.04%) yielded growth of Candida species.Methods: Candida was identified from Clinical samples by wet mount, Gram stain and Culture on SDA. The organisms were further speciated by germ tube test, Cornmeal agar Morphology, Sugar assimilation and Fermentation tests and CHROM agar. Antifungal susceptibility testing was done by disc diffusion method with Fluconazole (25 µg), Amphotericin-B(100U), Itraconazole(10 µg), Nystatin(50 µg), Clotrimazole(10 µg) and Voriconazole(1 µg).Results: C.tropicalis (46.79%) was the most common species isolated followed by C.albicans (37.17%) and C.parapsilosis (9.61%). Non albicans Candida species(NAC) (62.82%) was more than C.albicans (37.17%). All species isolated were susceptible to Amphotericin-B(100U), Nystatin(50 µg) and Voriconazole(1µg). Resistance to commonly used antifungal agents was Fluconazole-20.40%, Clotrimazole-18.26% and Itraconazole-17.34%.Conclusion: Species identification is important for treatment of Candida infections, as NAC species continue to be increasingly documented and not all species respond to same treatment.